BENTUK DAN FUNGSI WACANA SMS HUMOR PADA KETAWA.COM: BENTUK DAN FUNGSI WACANA SMS HUMOR PADA KETAWA.COM - Nur Indah Fitriani; Retno Danu Rusmawati (Universitas PGRI Adi Buana Surabaya, 2015)
SMS (Short Message Service is one of the written discourse form which is developing now. SMS (Short Message Service) is short message in text form which is on the cell phones media. Now, SMS is not Short Message Service anymore, but it has turned into Smile Message Service because SMS which is currently available now not only contains short message that is used to convey information but also as a means to convey humor ideas among the users. Therefore, now the SMS may be called as a form of humor discourse. Ketawa.com is one of the media on the internet that contains various kinds of humor SMS, in the form of words, sentences and discourse containing ideas of humor. The researchers used a qualitative methodology for generating descriptive data about the form and function of WSH on ketawa.com. The data was WSH in the form of words, sentences and discourse on ketawa.com edition June, 20th 2014 and the data source was ketawa.com. Data collection techniques which was used was a method of documentation by means of documenting data WSH on ketawa.com edition June, 20th 2014 by means copied into Microsoft Word document on the computer first, and then transferred to the thumb drive (USB). The results of data analysis in this research was discourse’s form of humor SMS on ketawa.com consists of forms of narrative discourse, expository discourse, hortatory discourse, exposition discourse, description discourse and the discourse of the puzzle. The most dominant of WSH form was discourse’e form of hortatory and descriptive. The function of humor SMS discourse on ketawa.com consisted of a function as a means of entertainment, education, social protest and as a media to edify or morals. The most dominant function of WSH was as a means of entertainment.